Becoming a strategist: the roles of strategy discourse and ontological security in managerial identity work - Mantere, S; Whittington, R (SAGE Publications, 2020)
What is the managerial identity work involved in becoming a ‘strategist’? Building on a rich, longitudinal set of interviews, we uncover three tactics through which managers mobilize the strategist identity. The self-measurement tactic uses strategy discourse as a normative measuring stick for evaluating the individual as a manager. The self-construction tactic uses strategy discourse as a blueprint for realizing career aspirations. The final self-actualization tactic uses strategy discourse as an emotional basis for crafting meaning into work. We find that strategy discourse can play both disciplinary and emancipatory roles, influenced by managers’ sense of ontological security. The paper highlights the importance of the social-psychological in strategist identity work and discusses implications for the contemporary opening up of strategy and for other similarly loosely-structured occupational groups.